Diversity of Arbuscular Mycorrhizae Fungi from Rhizosphere of Daemonorops draco Blume in Jambi: STATUS FUNGI MIKORIZA ARBUSKULA (FMA) PADA RIZOSFER JERNANG (Daemonorops draco Blume) DI JAMBI - Purwati, Betty; Budi, Sri Wilarso; Wasis, Basuki (Media Konservasi, 2019)
The research was conducted with the aim to analyze the diversity of arbuscular mycorrhizae fungi (AMF) from rhizosphere of Daemonorops draco Blume in Jambi. The sampling technique of soil and roots were done by propotional method. Sampling of the soil was carried out compositively at a depth of 0-20 cm and 20-40 cm, soil samples taken from jernang rhizosphere about 500 gram on each stem. Spores were isolated by wet filter pouring technique and continued with centrifugation, then the density of spores was measured and identified. The results showed an increasing number of spore and diversity of AMF. The identification results showed that the average number of spores was 106.39-209.46 spores per 20 gram of soil. The root colonization was in range of 39.25%-64.25%. The AMF diversity is 48 spores type AMF consists of 31 types of Glomus, 9 types of Acaulospora, 7 types of Scutellospora and 1 types of Gigaspora. Glomus has the highest spread rate at each depth. The relative abundance of the genus Glomus at both depths by 100%. The relative frequency of the genus Glomus also dominates at a depth of 0-20 cm is 92.27%, and soil at a depth of 20-40 cm is 95.05%. Keywords: AMF, Daemonorops draco Blume, Jambi